PENGARUH SUPERVISI KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU - ulya, uli uslihatul (Universitas Negeri Semarang, 2012)
Teachers performance is a job result that reached by teacher in perform duty assignment that is charged to them. In Fact there are many problems / con-straint that gets bearing with teacher performance, amongst those, not all teacher are develop Lesson Plan until maximal. where at in it don’t at education point entries nation character and has no it Explorations, Elaboration, Confirmation in activity fundamental learning. Then in teaching and learning interaction performing, not all teacher are utilize media and a variety learning model. Method that is utilized is not variation,only discourse and question-answer. Besides it, extant teacher which haven’t performed Action Research brazes. That thing because of headmaster su-pervision was not performed with best and teacher have not high job motivation. Problem formulation in this research is what exists positive influence headmaster supervision and teacher job motivation for economics-accountancy teachers perfor-mance in every SMA Negeri of Pemalang Regency whether simultan or partial.